MiR-152 influences osteoporosis through regulation of osteoblast differentiation by targeting RICTOR - Feng, Li (Pharm Biol, 2019)
Context: Evidence suggests that microRNA (miRNA) regulates gene expression and bone tissue homoeostasis of osteoporosis. MiR-152 has found to be abnormally expressed in osteoporosis, but its role in osteoblast differentiation has not been elucidated. Objective: To understand the potential mechanism of miR-152 in osteoblast differentiation via regulation of RICTOR. Materials and methods: The expression of miR-152 and RICTOR were tested in ovariectomized rat models of osteoporosis. Primary osteoblasts and MC3T -E1 cells were assigned into four groups, namely Control, miR-152 inhibitor, miR-control and miR-152 inhibitor + siRICTOR groups. qRT PCR and Western blots were performed to detect the expression of miR-152 and RICTOR, respectively. MTT assay was used to evaluate cell viability, and ALP activity determination and mineralization analyses were also conducted. Results: In ovariectomy-induced osteoporotic rats, miR-152 (3.06 ± 0.35) in femoral tissues increased significantly, while RICTOR (0.31 ± 0.04) decreased. Compared with the Control group, the miR-152 inhibitor group presented appreciable reduction of miR-152 in primary osteoblasts and MC3T3-E1 cells, as well as remarkable increases in RICTOR, p-Akt(s473)/Akt ratio, and osteogenesis-related genes, with enhanced cell viability, ALP activity and mineralization. In comparison with cells in the miR-152 inhibitor group, those in the miR-152 inhibitor + siRICTOR group had no observable difference in miR-152, but were dramatically up-regulated in RICTOR, as well as the corresponding opposite tendencies of other factors. Conclusion: Inhibiting miR-152 promoted osteoblasts differentiation and alleviated osteoporosis by up-regulating RICTOR. Therefore, miR-152 may be an essential mediator of osteoblast differentiation and a new therapeutic strategy for osteoporosis.